Tissue–Resident Memory T Cells in Chronic Inflammation—Local Cells with Systemic Effects? - Anoushka Ashok Kumar Samat; Jolijn van der Geest; Sebastiaan J. Vastert; Jorg van Loosdregt; Femke van Wijk (Cells, 2021)
Chronic inflammatory diseases such as rheumatoid arthritis (RA), Juvenile Idiopathic Arthritis (JIA), psoriasis, and inflammatory bowel disease (IBD) are characterized by systemic as well as local tissue inflammation, often with a relapsing-remitting course. Tissue–resident memory T cells (TRM) enter non-lymphoid tissue (NLT) as part of the anamnestic immune response, especially in barrier tissues, and have been proposed to fuel chronic inflammation. TRM display a distinct gene expression profile, including upregulation of CD69 and downregulation of CD62L, CCR7, and S1PR1. However, not all TRM are consistent with this profile, and it is now more evident that the TRM compartment comprises a heterogeneous population, with differences in their function and activation state. Interestingly, the paradigm of TRM remaining resident in NLT has also been challenged. T cells with TRM characteristics were identified in both lymph and circulation in murine and human studies, displaying similarities with circulating memory T cells. This suggests that re-activated TRM are capable of retrograde migration from NLT via differential gene expression, mediating tissue egress and circulation. Circulating ‘ex-TRM’ retain a propensity for return to NLT, especially to their tissue of origin. Additionally, memory T cells with TRM characteristics have been identified in blood from patients with chronic inflammatory disease, leading to the hypothesis that TRM egress from inflamed tissue as well. The presence of TRM in both tissue and circulation has important implications for the development of novel therapies targeting chronic inflammation, and circulating ‘ex-TRM’ may provide a vital diagnostic tool in the form of biomarkers. This review elaborates on the recent developments in the field of TRM in the context of chronic inflammatory diseases.